Current situation of Giardia and Cryptosporidium among Orang Asli (aboriginal) communities in Pahang, Malaysia - Mahdy, A.K.M.; Surin, J.; Lim, Yvonne Ai Lian; Al-Mekhlafi, M.S.H. (SEAMEO Regional Tropical Medicine and Public Health Network, 2007)
A cross-sectional study on the distribution of Giardia intestinalis and Cryptosporidium species was conducted among the Orang Asli communities at Pos Betau, Pahang, Malaysia. Fecal samples were collected from 316 participants, age between 1-76 years (156 males and 160 females). The samples were examined using trichrome staining technique for G. intestinalis, and Cryptosporidium species were detected using modified acid-fast staining technique. Biodata were also collected through a pre-tested standard questionnaire. The overall prevalence rates were 17.1 and 4.1, for giardiasis and cryptosporidiosis, respectively. The study indicated that there was a significant difference in the infection rate of G. intestinalis between age groups, with infections being higher in children (p < 0.05). However, cryptosporidiosis and giardiasis were not found to be gender biased. This study concludes that giardiasis and cryptosporidiosis are still public health problems in the Orang Asli communities in Malaysia, and special attention should be given to those in the high-risk groups.